The Effectiveness of BPKP Fraud Audit Finding on Determining the Level of Corruption in Indonesian Provinces - Chekat Fahmy Rosyadi; Tjerk Budding (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2017)
AbstractThis study aims to investigate the role of government auditing to restrain corruption. Hereby, it focuses on the effectiveness of performance of the Indonesian Finance and Development Supervisory Agency, known as Badan Pengawasan Keuangan dan Pembangunan (BPKP) as the internal auditor institution of the Indonesian President. The results show that BPKP fraud audit finding of irregularities has a positive relationship with the corruption level in Indonesian provinces. Data are used from provincial-level governments over the period 2012-2015 which produces 128 province-year observations. The study result shows that the irregularities found by BPKP fraud audit influence the level of corruption in the Indonesian provinces.